Interactive buckling tests on steel cones subjected to axial compression and external pressure - a comparison of experimental data and design codes - Ifayefunmi, Olawale (Taylor & Francis, 2014)
The plastic buckling of thick steel conical shells subjected to combined action of axial compression and external pressure is of considerable interest in the offshore and the nuclear industries. However, design information on this subject area is limited. At present, only the ASME B&PV code case 2286-2 provides design information for cones subjected to axial and hoop compressions acting simultaneously. This design rule has not been validated both experimentally and numerically, especially in the elastic–plastic region. Past results on interactive buckling tests carried out at the University of Liverpool, Liverpool, UK on 13 computer numerically controlled (CNC)-machined cones having r2/r1 = 2.02, r2/t = 34.3, h/r2 = 1.01, and β = 26.56◦ were compared with predictions of design loads obtained from ASME code case 2286-2. This was done in order to check the applicability of this design rule and suggest a safe operating region. The paper consider the general procedure adopted by the ASME case code 2286-2 to predict the interactive buckling curve and identifies some discrepancies in the predictions. It further suggests region of safe operational design level. Combined stability plots for the master cone and equivalent cylinder have also been derived. Results of this study show that ‘the equivalent cylinders’ do not represent a safe design substitute for a relatively thick cone under combined loading.